Utilization of green mussel shell waste for calcium carbonate synthesis through the carbonation method with temperature variation. Issue 1 (1st October 2022) - Prihanto, A; Muryanto, S; Ismail, R; Jamari, J; Bayuseno, AP
Abstract : In this study, PCC (precipitate calcium carbonate) was synthesized from green mussel shell waste via calcination and subsequent carbonation methods. Organic substances were removed from green mussel shell powder using a 5-hour calcination at 900 °C. Furthermore, the carbonation method was used in the Ca (NO3 )2 solution at constant stirring speed with pH control by NH4 OH, followed by the injection of carbon dioxide at 50, 70, and 90 °C temperature variations to precipitate calcium as CaCO3 (PCC). According to Rietveld's quantitative XRD analysis, PCC products at 50 °C, 70 °C, and 90 °C exhibited primarily calcite and aragonite phases, with a significant needle-like morphology of aragonite growth during synthesis. Aragonite growth appears to have increased with increasing temperature. The results show that a simple, low-cost approach to green recycling works.